Strongyloides stercoralis infection induces gut dysbiosis in chronic kidney disease patients. - Nguyen Thi Hai; Nuttanan Hongsrichan; Kitti Intuyod; Porntip Pinlaor; Manachai Yingklang; Apisit Chaidee; Thatsanapong Pongking; Sirirat Anutrakulchai; Ubon Cha'on; Somchai Pinlaor (Public Library of Science (PLoS), 2022)
Background Strongyloides stercoralis infection typically causes severe symptoms in immunocompromised patients. This infection can also alter the gut microbiota and is often found in areas where chronic kidney disease (CKD) is common. However, the relationship between S. stercoralis and the gut microbiome in chronic kidney disease (CKD) is not understood fully. Recent studies have shown that gut dysbiosis plays an important role in the progression of CKD. Hence, this study aims to investigate the association of S. stercoralis infection and gut microbiome in CKD patients. Methodology/principal findings Among 838 volunteers from Khon Kaen Province, northeastern Thailand, 40 subjects with CKD were enrolled and divided into two groups (S. stercoralis-infected and -uninfected) matched for age, sex and biochemical parameters. Next-generation technology was used to amplify and sequence the V3-V4 region of the 16S rRNA gene to provide a profile of the gut microbiota. Results revealed that members of the S. stercoralis-infected group had lower gut microbial diversity than was seen in the uninfected group. Interestingly, there was significantly greater representation of some pathogenic bacteria in the S. stercoralis-infected CKD group, including Escherichia-Shigella (P = 0.013), Rothia (P = 0.013) and Aggregatibacter (P = 0.03). There was also a trend towards increased Actinomyces, Streptococcus and Haemophilus (P > 0.05) in this group. On the other hand, the S. stercoralis-infected CKD group had significantly lower representation of SCFA-producing bacteria such as Anaerostipes (P = 0.01), Coprococcus_1 (0.043) and a non-significant decrease of Akkermansia, Eubacterium rectale and Eubacterium hallii (P > 0.05) relative to the uninfected group. Interesting, the genera Escherichia-Shigella and Anaerostipes exhibited opposing trends, which were significantly related to sex, age, infection status and CKD stages. The genus Escherichia-Shigella was significantly more abundant in CKD patients over the age of 65 years and infected with S. stercoralis. A correlation analysis showed inverse moderate correlation between the abundance of the genus of Escherichia-Shigella and the level of estimated glomerular filtration rate (eGFR). Conclusions/significance Conclusion, the results suggest that S. stercoralis infection induced gut dysbiosis in the CKD patients, which might be involved in CKD progression.